Реорганізація стаціонарних таборів для військовополонених в УРСР (1946–1950 рр.) - Потильчак, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
The author made complex analysis of forms and methods of organizational development of stationary camp net for prisoners of war on the territory of Soviet Ukraine during 1946–1950.